#TITLE_ALTERNATIVE# - NASUTION (NIM 13702033); Pembimbing : Dr. Ir. Aditianto Ramelan dan Hady Efendy, S.T., M., AKHMAYANDA
Refractory material is widely used for high temperature application in industry because its properties advantages, such as thermal shock resistance. One of the methods to increase the resistance of thermal shock is the application of short steel fiber reinforcement in the castable refractory. The non uniformly distributed steel fiber will affect the properties of refractory. This research was done to study the thermal shock resistance, apparent porosity and bulk density of castable LAMJ-1 (Alumina Spinel Castable) with woven and continuous steel fiber reinforcement after firing process at 1150oC. Composition and micro structure characterization were done using X-Ray Diffraction (XRD) and Scanning Electron Microscope XL-20 equipped with EDS DX-40. The testing of thermal shock resistance was carried out at 1200oC for 30 minutes and then the specimen was cooled in water and this process was done repeatedly until weight loss of the specimen reached 40% of the initial weight one. Apparent porosity and bulk density were measured based on ASTM C 20-83. The cycles of thermal shock resistance for castable refractory without steel fiber reinforcement are higher than specimen with steel fiber reinforcement. Castable refractory without steel fiber reinforcement achieved 18.33 cycles and specimen with steel fiber reinforcement is 13.33 cycles. Bulk density of castable refractory without steel fiber reinforcement is 2.74 gr/cm3 and for steel fiber reinforcement is 2.84 gr/cm3. Apparent porosity of castable refractory without steel fiber reinforcement is 19.5% and specimen with steel fiber reinforcement is 18.4%. Further investigations should be carried out to study the decrease mechanism of thermal shock resistance by using steel fiber. Failure on steel fiber reinforcement castable refractory was affected by oxidation of steel. Generally, the fracture area of specimen was happened on woven steel.